Reducing PNS with minimal performance penalties via simple pulse sequence modifications on a high-performance compact 3T scanner - Myung Ho In (2020)
© 2020 Institute of Physics and Engineering in Medicine. One of the major concerns associated with high-performance gradients is peripheral nerve stimulation (PNS) of the subject during MRI exams. Since the installation, more than 680 volunteer subjects (patients and controls) have been scanned on a compact 3 T MRI system with high-performance gradients, capable of 80 mT m-1 gradient amplitude and 700 T m-1 s-1 slew rate simultaneously. Despite PNS concerns associated with the high-performance gradients, due to the smaller physical dimensions of the gradient coils, minimal or no PNS sensation was reported with most pulse sequences. The exception was PNS reported by only five of 252 subjects (about 2%) scanned with a specific 3D fast spin echo pulse sequence (3DFLAIR). Rather than derating the entire system performance across all pulse sequences and all gradient lobes, we addressed reported PNS effect with a simple and specific modification to the targeted lobes of the problematic pulse sequence. in addition, the PNS convolutional model was adapted to predict sequence-specific PNS threshold level and its reduction after derating. The effectiveness of the targeted pulse sequence modification was demonstrated by successfully re-scanning four of the subjects who previously reported PNS sensations without further reported PNS. The pulse sequence modification did not result in noticeable degradation of image quality or substantial increase in scan time. The results demonstrated that PNS was rarely reported on the compact 3 T, and when it was, utilizing a specific modification of the gradient waveform causing PNS was an effective strategy, rather than derating the performance of the entire gradient system.